The Right of Inheritance of the Second Wife According to the Civil Code (Study of Supreme Court Decision Number 942/K/Pdt/2022) - Wiliam Antonius; Amad Sudiro (Pusat Publikasi Nusantara, 2023)
This research discusses the inheritance system according to civil law in Indonesia. One of the cases that was the focus of the research was a dispute regarding the right to inherit a house in the Supreme Court decision Number 942/K/PDT/2022 involving Amin Sudartio and Fong A Foe alias Mrs. Mey. In this case, Amin Sudartio was initially recognized as the legal heir by the North Jakarta District Court, but the DKI Jakarta High Court declared Amin Sudartio's claim unclear and then the decision was annulled by the DKI Jakarta High Court. The Supreme Court also rejected Amin Sudartio's cassation request, resulting in the cancellation of the initial decision recognizing him as the legal heir. This research also discusses legal considerations and the implications of the court decision in this case. This research uses normative juridical methods and a statutory approach to discuss the inheritance rights of second wives according to the Civil Code. This study highlights the inheritance rights of second wives in second marriages and the inheritance rights of children or descendants. This research aims to determine the inheritance rights of the second wife according to the Civil Code and the extent of the rights obtained by the wife in the second marriage. In general, inheritance is a legal system that regulates the transfer of inherited assets from a deceased person to heirs or appointed people. The Civil Code differentiates between ab-intestato heirs and heirs, and determines who has the right to inherit according to law. Apart from that, this research also emphasizes the importance of inheritance law in providing legal certainty in resolving problems related to the transfer of assets after a person's death